Содержание договора суррогатного материнства - Коренга, Юлія Володимирівна; Korenha, Yuliia V. (Ministerul Justiţiei al Republicii Moldova, 2013)
This paper studies the theoretical problems of the conditions of a civil contract in the context of a comparative analysis with the agreement of surrogacy. The author conducts research material, regular and random conditions of the contract of surrogacy is studied in detail the subject of the contract. The main aim of the paper is seen extensive development of contract surrogacy, because this agreement is to ensure protection of the rights and obligations of the parties. In order to examine the content of the contract surrogacy author analyzes in detail each of the terms of this agreement.

В статье изучаются теоретические проблемы условий гражданско-правового договора в контексте сравнительного анализа с договором суррогатного материнства. Автор проводит исследование существенных, обычных и случайных условий договора суррогатного материнства, детально изучается предмет договора. Основной целью статьи есть детальная разработка условий договора суррогатного материнства, ведь данный договор должен гарантировать защиту прав и обязанностей сторон. Для того, чтобы изучить содержание договора суррогатного материнства автор детально анализирует каждую из условий данного договора.
Keywords: surrogacy contract; maintenance contract surrogacy; the essential terms of the contract surrogacy; conventional surrogacy contract terms; the random terms of surrogacy; the subject of the contract; договор суррогатного материнства; содержание договора суррогатного материнства; существенные условия договора суррогатного материнства; обычные условия договора суррогатного материнства; случайные условия договора суррогатного материнства; предмет договора